Q fever vaccination: Australian animal science and veterinary students' One Health perspectives on Q fever prevention - Md R. Rahaman; Adriana Milazzo; Helen Marshall; Anne-Lise Chaber; Peng Bi (Taylor & Francis Group, 2021)
Unvaccinated animal science and veterinary students are at risk of Q fever, a vaccine-preventable zoonotic disease transmitted from animals to humans. We investigated students' perspectives on Q fever prevention using a One Health approach combining animal, human and environmental health. Animal science and veterinary students enrolled at the University of Adelaide in 2019 were invited to participate in an online survey to explore their perceptions about Q fever and prevention strategies. We undertook descriptive analysis and logistic regression. Overall, 46% of students reported little to no knowledge of Q fever. Over three-quarters of students reported transmission of Q fever via aerosol inhalation and animal culling, whilst other modes including sexual transmission between humans (7%) was poorly identified. The majority of students reported exposure to cattle, sheep and goats. Of those who reported vaccination status, 5% veterinary and 61% animal science students were unvaccinated for Q fever. Challenges concerning vaccination included cost, time and access to healthcare with strategies aimed at promoting awareness, improving healthcare access and subsidized and mass vaccination. Knowledge of Q fever among respondents, particularly about disease transmission was suboptimal. As a key principle to One Health approach, adherence to biosecurity guidelines during contact with animals could potentially reduce zoonoses including Q fever transmission. Improving access to Q fever vaccine for unvaccinated students is a priority. Findings underscore that university policy for Q fever vaccination needs to consider subsidized vaccination for both animal science and veterinary students.